Towards A Value-Dominant Logic of Marketing - Hastings, Hunter (2019)
Inspired by Vargo & Lusch’s Service-Dominant Logic (SDL) and relying on the Austrian School’s individualism and subjectivism, we use knowledge from economics to better support the discussion of the primary topic of Marketing: that of value creation. Specifically, we draft a Value-Dominant Logic. We provide ten foundational premises stemming from the recognition that value is subjective and, consequently, cannot be created by entrepreneurs or firms. Entrepreneurs and firms propose value, but subjective value can only be perceived, created and thus experienced in the individual consumer’s mind. By adopting the perspective that logically follows from this understanding, the disciplines of management and marketing will be better able to narrow the uncertainties of the market process, and entrepreneurs can make better decisions about how to help consumers overcome felt uneasiness by adopting their proposed solutions.